2021
DOI: 10.1002/jbm.b.34896
|View full text |Cite
|
Sign up to set email alerts
|

Polybutylene succinate artificial scaffold for peripheral nerve regeneration

Abstract: Regeneration and recovery of nerve tissues are a great challenge for medicine, and positively affect the quality of life of patients. The development of tissue engineering offers a new approach to the problem with the creation of multifunctional artificial scaffolds that act on various levels in the damaged tissue, providing physical and biochemical support for the growth of nerve cells. In this study, the effects of the use of a tubular scaffold made of polybutylene succinate (PBS), surgically positioned at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…The scaffolds consist of large surface area, high porosity, and good elasticity which afforded the scaffolds with facilitated cell proliferation. The development of artificial scaffolds for peripheral nerve regeneration using electrospinning was demonstrated by Cicero and colleagues [49]. The resultant 3D PBS-based scaffolds were flexible thin sheets with diameters ranging between 1-5 microns.…”
Section: Pbs-based Materials For Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…The scaffolds consist of large surface area, high porosity, and good elasticity which afforded the scaffolds with facilitated cell proliferation. The development of artificial scaffolds for peripheral nerve regeneration using electrospinning was demonstrated by Cicero and colleagues [49]. The resultant 3D PBS-based scaffolds were flexible thin sheets with diameters ranging between 1-5 microns.…”
Section: Pbs-based Materials For Tissue Engineeringmentioning
confidence: 99%
“…The clinical studies of PBS-based scaffolds have been conducted using rats in various labs such as Istituto Zooprofilattico Sperimentale della Sicilia in Italy which was authorized by the Ministry of Health. The findings indicated that PBS scaffold has the potential as an implantable material for improving the regeneration of injured tissue in rats as well as shortening the time for nerve regeneration [49]. However, to the best of our knowledge, there is no study performed clinical trials on humans.…”
Section: Current Status and Future Directionsmentioning
confidence: 99%
“…It has excellent processability and proven biocompatibility making it a promising polymer for various biomedical applications [ 13 , 14 ]. Recently, a planar PBS microfibrillar scaffold was successfully implanted in a rat model, as a nerve regeneration tool [ 15 ]. A recent study demonstrated complete biodegradability and the absence of inflammation in high-resolution MRI investigation, showing complete reabsorption by 120 days post-implant [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cicero et al used PBS as a planar microfibrillar scaffold implanted as a conduit, in a rat model, to preserve nerve continuity and promote its regeneration. They observed biodegradability from high resolution MRI investigation showing complete reabsorption in 120 days post implant [ 26 ]. Almeida et al produced and characterized anisotropic planar scaffolds through weft knitting.…”
Section: Introductionmentioning
confidence: 99%